Principal Transformational Leadership in Improving Teacher and School Staff Performance - Fahmi, Ahmad Khoirur Rijal; Yuwanita, Ary; Faiza, Dwi Eni Nur (Faculty of Education Universitas Negeri Malang, 2021)
The focus of this research aims to determine the role of the principal's transformational leadership in improving staff and teacher performance. This study uses the literature review method. The author reviewed various literature on the strategies of principals as transformational leaders in improving the performance of teachers and school staff sourced from the latest scientific journals. The results we get are that the principal's transformational leadership can change a person from the basic thoughts and behaviors that underlie the person about carrying out the assigned tasks and into an effective leadership style to produce constant performance and tends to increase.